Komunikacja niewerbalna: rola gestów ilustruj cych w komunikacji - Jarmołowicz, Ewa (Investigationes Linguisticae, 2004)
This  article has a twofold purpose. First, to show that gestures and speech are fully integrated and together realize a common communicative aim. That is why, as it will be shown, taking both verbal and nonverbal components under consideration is necessary for the correct understanding of  the speaker's intention. Second, to emphasize the role of gestures in the process of communication. The function of gesture in communication  is often attributed to the verbal component. It will be  shown, on the base of a few examples, that gestures are crucial for the interpretation of messages. The  analyzed examples are taken from the TV programmes such as Polish and American talk – shows and concern the gestures classified by P. Ekman and W. Friesen as illustrators.